Synthesis and structural characterization of a lithium alkynyl(hydrazinediido)zirconate and its protonolysis to an alkynylhydrazido(1-)zirconium complex - Gehrmann, Thorsten; Wadepohl, Hubert; Gade, Lutz H. (Zeitschrift für anorganische und allgemeine Chemie, 2015)
Reaction of the hydrazinediido complex 1 with lithiated phenylacetylene selectively gave the lithium alkynyl(hydrazinediido)zirconate [(N2TBSNpy)Zrμ-NNPh2-1κN:2κNμ-PhCC-1κC:2κC-Li(py)] (2), which reacted with one molar equivalent of TMEDA to give the corresponding Li-TMEDA derivative [(N2TBSNpy)Zrμ-NNPh2-1κN:2κNμ-PhCC-1κC:2κC-Li(TMEDA)] (3). The details of the molecular structure of complex 3 were established by single-crystal X-ray structure analysis. The lithium hydrazinediidozirconate 2 was treated with triethylammonium hydrochloride yielding the corresponding alkinylzirconium hydrazido(1-) complex 4 as a mixture of two diastereomers.
First published: 22 May 2014
Gesehen am 10.08.2021